STRATEGI HUBUNGAN MASYARAKAT DALAM MENINGKATKAN PENERIMAAN PESERTA DIDIK BARU - Moh. Rofiki; Nur Siska Aprilia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the public relations strategy for increasing new student enrollment at SD Muhammadiyah 1 Paiton. Using a case study-based qualitative approach, this research explores the various promotional methods applied by the school's public relations, including the utilization of social media, organizing open houses, cooperation with kindergartens/early childhood, and fostering public relations. The results showed that well-planned and innovative PR strategies contributed significantly to the increase in the number of new students. The application of social media as a means of communication and promotion, as well as active interaction with audiences, are key factors in attracting prospective students and parents. In addition, open house programs and collaboration with other educational institutions also support the effectiveness of new student enrollment campaigns. With a sustainable and research-based strategy, SD Muhammadiyah 1 Paiton is able to increase its competitiveness in the world of education.